Analisis Faktor Penerimaan Pengguna ChatGPT dengan Menggunakan Metode TAM pada Mahasiswa Universitas Amikom Purwokerto - Nurul Hani; Putri Vidia Lestari; Hanenda Putri Zamora; Ratri Ismayanti; Ito Setiawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In the 5.0 industrial revolution, the field of education has been impacted by the sophistication of technology. The use of ChatGPT, commonly known as AI, greatly assists users in obtaining information, one of which is the use of ChatGPT among students in completing their assignments. This research aims to analyze the factors influencing the acceptance of ChatGPT users using the Technology Acceptance Model (TAM) method among students at Amikom Purwokerto University. The TAM method is used to evaluate two main variables, namely Perceived Usefulness (PU) and Perceived Ease of Use (PEOU), as well as their impact on user attitude (Attitude Toward Using), intention to use (Behavioral Intention to Use), and actual usage by users (Actual System Use). This research uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to students of Universitas Amikom Purwokerto. The analysis results show that PU and PEOU have a significant influence on user attitudes, which affects the intention to use ChatGPT, encouraging users to use ChatGPT more frequently in their activities.